1999
DOI: 10.1063/1.370647
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dispersive x-ray diffraction and Raman scattering of Zn1−xMnxSe bulk crystals at high pressure

Abstract: Energy-dispersive x-ray diffraction experiments were carried out to investigate the structure of phase transitions under high pressure. It was found that the zinc blende (B3) to rock salt (B1) phase transition pressures of Zn0.93Mn0.07Se and Zn0.76Mn0.24Se bulk crystals are found 11.8±1.5 and 9.9±0.5 GPa, respectively. The respective bulk moduli are 61.8±0.8 and 60.5±0.8 GPa. The pressure-induced zinc blende (ZB) to rock salt (RS) structure phase transition is interpreted as a signature of the semiconductor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
4
8
1
Order By: Relevance
“…3. At the lower pressure like 0.1 GPa, the LO and TO phonon modes are observed at about 251 and 205 cm −1 , respectively, which are in agreement with related reports [19,25]. With increasing pressure up to about 5.5 GPa, the TO phonon mode splits into two peaks.…”
Section: High-pressure Raman Scatteringsupporting
confidence: 91%
“…3. At the lower pressure like 0.1 GPa, the LO and TO phonon modes are observed at about 251 and 205 cm −1 , respectively, which are in agreement with related reports [19,25]. With increasing pressure up to about 5.5 GPa, the TO phonon mode splits into two peaks.…”
Section: High-pressure Raman Scatteringsupporting
confidence: 91%
“…Generally, it may be concluded that wurtzite-type Zn 0.53 Mg 0.47 Se is stable at pressures studied in this work. This observation is in agreement with expectations based on the known behaviour of Zn 1−x Mg x Se [18] as well as ZnSe alloyed with iron and manganese [19,20]. The transition point is ∼8.5 GPa according to the extrapolated data (phase transition points determined from a change of optical properties) from Ref.…”
Section: Resultssupporting
confidence: 91%
“…Our sample was of wurtzite-type, but a similar bonding type justifies performing such extrapolation. For related Zn 0.84 Fe 0.16 Se and Zn 0.76 Mn 0.24 Se compounds the transition points are comparable: the tetrahedral structure remains stable up to about 10 GPa [19,20], i.e. in about twice as wide pressure range than that applied in the present study.…”
Section: Resultssupporting
confidence: 44%
See 2 more Smart Citations